PHYTOCHEMICAL SCREENING WITH LC-HRMS PROFILING AND IN VITRO BIOLOGICAL ACTIVITIES OF ARGYREIA CUNEATA (L.) AND ARGYREIA SETOSA (L.). - Kale, Sandip; Kirdat, Pranoti; Kale, Suresh; Dandge, Padma (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The present study was designed for phytochemical screening and biological activities of Argyreia cuneata (L.) and Argyreia setosa (L.) medicinal plants. Methods: The mature leaves of A. cuneata (L.) and A. setosa (L.) were extracted with methanol (Ac-Me, As-Me) and ethyl acetate (Ac-EA, As-EA) solvent followed by qualitative and quantitative phytochemical analysis. Antimicrobial activity was evaluated by agar well diffusion method, whereas the activities such as antioxidant, antidiabetic, and anti-inflammatory were determined by in vitro methods. Liquid chromatography-high-resolution mass spectroscopy (LC-HRMS) was used to recognize the bioactive components. Results: The highest phenolic content (0.840±0.130 mg GAE/ml extract) reported from As-Me and for flavonoids 0.128±0.012 mg QE/ml from Ac- EA. The Ac-Me exhibited higher inhibition zone against all the bacteria used for study. In antioxidant activity, Ac-Me and Ac-EA report highest 2,2 dipheny l,1 picryl hydrazine (IC50=0.580±0.012 mg/ml) and nitric oxide radical scavenging potential (IC50=0.772±0.059 mg/ml), respectively. For antidiabetic activity, As-Me showed highest α-amylase inhibition activity as well as glucose adsorption. In anti-inflammatory activity, Ac-EA exhibits highest (IC50=0.529±0.009 mg/ml) protein denaturation inhibition and Ac-Me showed highest (91.56±1.96%) HRBC hemolysis inhibition. The LC-HRMS analysis of methanolic extract reports the majority of phenolic compounds. Conclusion: The study showed that the plants A. cuneata (L.) and A. setosa (L.) are well exploited and can be used for the source of potent natural bioactive components. This study also may thereby provide an insight in screening of crude drug.